2010
DOI: 10.1038/ki.2010.134
|View full text |Cite
|
Sign up to set email alerts
|

Circulating high-molecular-weight RAGE ligands activate pathways implicated in the development of diabetic nephropathy

Abstract: The accumulation of advanced glycation end products is thought to be a key factor in the initiation and progression of diabetic nephropathy. Here we determined whether the size of the ligands for the receptor for advanced glycation end products (RAGEs) that were present in the serum of patients with type 2 diabetes modulates their pathogenic potential. Serum was collected from control subjects and patients with type 2 diabetes with varying degrees of renal disease (normo-, micro-, or macroalbuminuria). The tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 31 publications
1
46
0
1
Order By: Relevance
“…11 HMGB1, a nuclear protein that regulates gene transcription, is passively released after cell injury and has been implicated in tissue inflammation in animal models of kidney injury. 13,30 HMGB1 is a known ligand of TLR, which leads to the activation of NF-kB, ultimately increasing tissue inflammation. 12,31 We also found that renal expression of HMGB1 was decreased in mice given LC15-0444 treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 HMGB1, a nuclear protein that regulates gene transcription, is passively released after cell injury and has been implicated in tissue inflammation in animal models of kidney injury. 13,30 HMGB1 is a known ligand of TLR, which leads to the activation of NF-kB, ultimately increasing tissue inflammation. 12,31 We also found that renal expression of HMGB1 was decreased in mice given LC15-0444 treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A 2012 paper proposed HMGB-1 as a causative factor in renal damage. 13 DPPIV has high expression levels and activity in the kidney, and is found on the apical/brush border surface of proximal renal tubular cells and in the urine. 14 However, the roles of DPPIV and its inhibition are not fully understood in the pathogenesis of renal disease.…”
mentioning
confidence: 99%
“…They can interact with their receptor (RAGE) and induce inflammatory responses and ROS generation (Schmidt et al, 1995), cardinal features of diabetic nephropathy. In vivo experiments have demonstrated that the AGE-RAGE interaction generates superoxide and may contribute to angiopathy development in type 2 diabetes (Penfold et al, 2010). Further, in diabetic patients, glycated albumin induces ROS production in endothelial cells (Rodino-Janeiro et al, 2010).…”
Section: Role Of Reactive Oxygen Species In Diabetes Sources Of Reactmentioning
confidence: 99%
“…RAGE activation by high serum and tissue levels of AGEs induces multiple intracellular signalling pathways (Figure 4) that have been implicated in pathogenesis of serious diabetic complications such as enhanced atherosclerosis, cardiovascular disease, nephropathy and chronic inflammation [9,10,[108][109][110] . It has been documented that circulating AGEs bind with endothelial RAGE resulting in endothelial dysfunction via activation of a number of signaling pathways, e.g., activation of nicotinamide adenine dinucleotide phosphate oxidase that enhances the production of reactive oxygen species (ROS) [108] .…”
Section: Intracellular Effects Of Age-rage Binding On Cardiovascular mentioning
confidence: 99%